THE EFFECT OF COMPLETE FEED SUBSTITUTION WITH COFFEE PEEL WASTE ON THE PERFORMANCE OF THE FINISHER PHASE PIGS - Mien T.H Lapian, Petrus R.R.I Montong. Hapry F.N.Lapian, (Chelonian Research Foundation, 2024)
The primary objective of this research was to assess the impact of incorporating coffee husk waste as a complete feed replacement ingredient on pig performance. A total of 36 crossbred pigs, originating from Sterbyderby and Kirk, Topper and Exotic, and Abraham and Kirk, were subjected to a comprehensive study employing a 4-treatment, 3-repetition design. The analysis of variance (ANOVA) revealed that the inclusion of coffee husk waste as a partial substitute for the ration, alongside various treatment methods such as sun-dried, soaked, and boiled coffee husks, exhibited no statistically significant differences (P>0.05) in ration consumption. However, the study did unveil significant differences (P<0.01) in body weight gain and ration efficiency (P<0,05) at the coffee skin substitution level. In contrast, The specific treatment of coffee skin had no significant impact on both body weight gain and ration efficiency (P>0.05), and the interaction between the two factors also did not yield significant differences (P>0.05). In summary, this study affirms the potential of coffee skins as a substitute feed ingredient in select pig rations, with the most promising outcomes observed at a 5% substitution level with boiled treatment. Keywords: Substitution, Coffee Peel, Pig farming